Assessment of the potential for district heating in four major eastern cities: Washington, D. C. , Philadelphia, Baltimore, and Boston - Bernow, S S; Rosen, R A (Energy Systems Research Group, Inc., Albany, NY (USA), 1978)
This study assesses the potential functional and economic advantages of district-heating systems for providing the heating, cooling, and hot-water energy needs of Washington, D.C., Philadelphia, Baltimore, and Boston. Thermal energy demand, demand coefficients, and costs of thermal energy using conventional systems are considered. Finally, the design of district-heating systems is discussed in terms of distribution networks, costs, and payback from fuel savings.